PMO-129 Relaxin reduces portal hypertension through stimulation of hepatic nitric oxide production. (28th May 2012) - Fallowfield, J; Snowdon, V; Aucott, R; Gordon-Walker, T; Pellicoro, A; Iredale, J
Abstract : Introduction: We have previously reported that the multifunctional hormone relaxin (RLX) downregulated the activation state and contractility of hepatic myofibroblasts and reduced portal hypertension (PHT) in cirrhotic rats (Fallowfield J et al BASL 2010). RLX has been shown to induce a range of haemodynamic effects in different organs and species, largely through effects on nitric oxide (NO). In cirrhosis, there is hepatic NO deficiency and hyporesponsiveness. We postulated that the effects of RLX on PHT were, at least in part, mediated by activation of the NO pathway. Methods: Cirrhosis and PHT was induced in age-matched male Sprague-Dawley rats by 8 weeks biweekly i.p. CCl4, before randomisation to the following groups: (1) recombinant human H2-relaxin (H2-RLX) s.c. for 72 h; (2) placebo s.c. for 72 h; (3) H2-RLX s.c. + L-NAME p.o. for 72 h; (4) placebo s.c. + L-NAME p.o. for 72 h; n =5–10/group. NO levels in serum were determined by quantitative immunoassay for total nitrite and hepatic NO bioavailability by cGMP immunoassay. Relative levels of Ser 473 phosphorylated Akt (p-Akt) and Ser 1179 phosphorylated eNOS (p-eNOS) protein in whole liver extracts were quantified by Western blotting. Rho-kinase activity was assessed by phosphorylation of the endogenous Rho-kinase substrate moesin (Thr 558 ). Portal pressure (PP) and mean arterial pressure (MAP) were measured under general anaesthesia by direct cannulation. Results: Rats treated with CCl4 for 8 weeks developed micronodular cirrhosis, splenomegaly and PHT. There was no difference in mean serum nitrite levels between H2-RLX and placebo treated rats. However, H2-RLX increased hepatic cGMP production (p<0.01) and upregulated expression of p-Akt (p<0.05) and p-eNOS (p<0.05) protein. In contrast, there was no difference in p-moesin levels. H2-RLX treated animals had a lower mean PP than placebo controls (11.6±0.3 mm Hg [95% CI 10.97 to 12.81] vs 9.2±0.6 mm Hg [7.66 to 10.7]; p=0.008) and decreased spleen size (p=0.01). The portal hypotensive effect of H2-RLX was abrogated by co-administration of the NOS inhibitor L-NAME (11.42±0.35 mm Hg [10.44 to 12.4]; p=0.004 vs H2-RLX). MAP was comparable in RLX and placebo treated animals that also received L-NAME. Conclusion: A reduction in NO bioavailability is considered to be a major factor increasing intrahepatic vascular tone in cirrhosis. Our data indicate that H2-RLX was capable of stimulating intrinsic (but not systemic) NO generation in fibrotic liver by activating the Akt/eNOS/cGMP pathway. Furthermore, inhibition of this axis with L-NAME ablated the portal hypotensive effect of H2-RLX, suggesting that it could represent a novel liver-specific NO donor in cirrhotic PHT. Competing interests: None declared.